2021
DOI: 10.3389/fpsyg.2021.767784
|View full text |Cite
|
Sign up to set email alerts
|

Improving Health of People With Multiple Sclerosis From a Multicenter Randomized Controlled Study in Parallel Groups: Preliminary Results on the Efficacy of a Mindfulness Intervention and Intention Implementation Associated With a Physical Activity Program

Abstract: Objectives: The objective of this study is to investigate the efficacy of psychological Interventions – Mindfulness or Implementation Intention – associated with a Physical Activity program, delivered via internet, in reducing Multiple Sclerosis symptoms.Method: Thirty-five adults were randomly assigned to one of the three groups: a Mindfulness-Based Intervention group (N = 12), Implementation Intention group (N = 11), and a Control Group (N = 12). All the groups received the same Physical Activity program. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 128 publications
(132 reference statements)
1
10
0
Order By: Relevance
“…Following deduplication and the addition of four further studies identified via reference list searching there were 1,312 potential studies for inclusion. After title and abstract screening, 30 full text studies were reviewed, of which 14 were included in the final analyses [50][51][52][53][54][55][56][57][58][59][60][61][62][63] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following deduplication and the addition of four further studies identified via reference list searching there were 1,312 potential studies for inclusion. After title and abstract screening, 30 full text studies were reviewed, of which 14 were included in the final analyses [50][51][52][53][54][55][56][57][58][59][60][61][62][63] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the 14 studies reported carrying out power calculations to determine necessary sample size [52, 55, 56, 58-60, 62, 63]; of the remaining, five did not [51,53,57,58,61] and one provided insufficient detail [54]. Studies took place across four continents, in eight different countries: three from Iran [54,57,63], two from Italy [55,56], the UK [51,53], Australia [59,61], the USA [50,60], and one each from Switzerland [52], Canada [62], and France [58]. Sample size ranged from 21-150.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations